The characterisation of genes from a genetic screen that promote invasion - Taylor, Louisa (2018)
Metastasis accounts for over 90% of cancer mortality. The first step of metastasis is the invasion of cancer cells into the tissue and vasculature surrounding the tumour. Despite its clinical importance, our understanding of invasion and its genetic determinants is limited. A large-scale, loss-of-function genetic screen in Drosophila melanogaster has recently been completed in the Georgiou Lab which identified a number of genes that may promote cellular invasion upon their depletion in the Drosophila epithelium. This project will focus on the characterisation of some of these hits.